Emergency general surgery 'Hot Clinics' reduce admission rates and duration of inpatient stay. Issue 1 (14th December 2015) - Th'ng, Francesca; Skouras, Christos; Paterson-Brown, Alice; Ravindran, Rajan; Lamb, Peter; de Beaux, Andrew; Paterson-Brown, Simon; Mole, Damian J
Abstract : Objective: To determine the impact of a 'Hot Clinic' (HC) on emergency general surgery patient flow-through. Design: Prospective service evaluation study. Setting: HC is a four-bedded area coordinated by a specialist nurse. The HC consultant sees emergency patients referred from the emergency department, general practitioners or those in preceding 24 h considered suitable for interim discharge while awaiting investigations and HC reassessment. Patients: All patients with acute abdominal pain were evaluated in three 4 week groups: before (group 1), 1 month (group 2) and 6 months after the HC was introduced (group 3). Interhospital transfers, intrahospital ward referrals and trauma patients were excluded. Intervention: Introduction of consultant-led surgical HC every weekday afternoon. Main outcome measures: Proportion of patients admitted under general surgeons, length of inpatient stay and the proportion of patients referred again within 3 months were investigated. Results: 1409 patients were referred, of which 1061 met the inclusion criteria: 307 in group 1, 326 in group 2 and 428 in group 3. There was no difference in gender distribution (p=0.759). Inpatient admissions were significantly reduced (85.0% vs 78.2% vs 54.4%; p<0.001) and the inpatient duration of stay was significantly shorter after HC introduction (median (IQR) (95% CI) 63.8 (29.0–111.6) (51.8 to 72.8) hours vs 48.8 (21.7–101.2) (42.0 to 55.6) hours vs 47.7 (20.9–92.7) (42.8 to 56.9) hours; p=0.011). Conclusions: Emergency general surgery HCs are associated with significant reductions in admission rates and inpatient bed occupancy. This service redesign has the potential to dramatically relieve pressure on acute surgical services.